An Updated Review: Emerging Anticonvulsants - Siddiqui, Nadeem (International Journal of Pharmaceutical & Biological Archive, 2011)
Anticonvulsants are a diverse group of pharmaceuticals used in the treatment of epileptic seizures. The goal of an anticonvulsant is to suppress the rapid and excessive firing of neurons that start a seizure. The use of current antiepileptic drugs has been questioned due to the non selectivity of the drugs and the undesirable side effects posed by them.This lead to the search for antiepileptic compounds with more selective activity and lower toxicity continues to be an area of investigation in medicinal chemistry. This review describes various moieties representing anticonvulsant activity.